The work programme of EURADOS on internal and external dosimetry. (October 2018) - Rühm, W.; Bottollier-Depois, J.F.; Gilvin, P.; Harrison, R.; Knežević, Ž.; Lopez, M.A.; Tanner, R.; Vargas, A.; Woda, C.
Since the early 1980s, the European Radiation Dosimetry Group (EURADOS) has been maintaining a network of institutions interested in the dosimetry of ionising radiation. As of 2017, this network includes more than 70 institutions (research centres, dosimetry services, university institutes, etc.), and the EURADOS database lists more than 500 scientists who contribute to the EURADOS mission, which is to promote research and technical development in dosimetry and its implementation into practice, and to contribute to harmonisation of dosimetry in Europe and its conformance with international practices. The EURADOS working programme is organised into eight working groups dealing with environmental, computational, internal, and retrospective dosimetry; dosimetry in medical imaging; dosimetry in radiotherapy; dosimetry in high-energy radiation fields; and harmonisation of individual monitoring. Results are published as freely available EURADOS reports and in the peer-reviewed scientific literature. Moreover, EURADOS organises winter schools and training courses on various aspects relevant for radiation dosimetry, and formulates the strategic research needs in dosimetry important for Europe. This paper gives an overview on the most important EURADOS activities. More details can be found atwww.eurados.org .